Research on Security System of Smart Home Based on ZigBee - Du, Yuhan (International Journal of Computer Science and Information Technology, 2024)
In view of the drawbacks of traditional smart home using wired layout, and the problem that it can not accurately transmit and integrate home information, this paper proposes a new type of smart home using ZigBee protocol in wireless sensor network compared with the advantages of traditional smart home. This paper introduces a smart home system based on CC2530 wireless MCU ZigBee network nodes. The remote monitoring system is applied to the smart home environment under the ZigBee protocol, which is used to better deal with the security problems of smart home.